Development of Potent Inhibitors of Fatty Acid Amide Hydrolase Useful for the Treatment of Neuropathic Pain. (30th August 2018) - Brindisi, Margherita; Borrelli, Giuseppe; Brogi, Simone; Grillo, Alessandro; Maramai, Samuele; Paolino, Marco; Benedusi, Mascia; Pecorelli, Alessandra; Valacchi, Giuseppe; Di Cesare Mannelli, Lorenzo; Ghelardini, Carla; Allarà, Marco; et al.
Abstract: The unique role of fatty acid amide hydrolase (FAAH) in terminating endocannabinoid (EC) signaling supports its relevance as a therapeutic target. Inhibition of EC metabolizing enzymes elicits indirect agonism of cannabinoid receptors (CBRs) and therapeutic efficacy devoid of psychotropic effects. Based on our previous ligands, and aiming at the discovery of new selective FAAH inhibitors, we developed a series of 12 new compounds characterized by functionalized tricyclic scaffolds. All the developed compounds display negligible activity on monoacylglycerol lipase (MAGL) and CBRs. The most potent FAAH inhibitors of the newly developed series, 6‐oxo‐5, 6‐dihydro‐4 H ‐benzo[ f ]pyrrolo[1, 2‐ a ][1, 4]diazepin‐9‐yl‐6‐phenylhexylcarbamate (5 h ) and 4‐oxo‐5, 6‐dihydro‐4 H ‐benzo[ f ]pyrrolo[1, 2‐ a ][1, 4]diazepin‐9‐yl‐(6‐phenylhexyl)carbamate (5 i ) (nanomolar FAAH inhibitors, the latter of which also shows micromolar affinity at the CB1 R), were selected for further studies. Results of cell‐based studies on a neuroblastoma cell line (IMR32) demonstrated5 h, 5 i, and our reference compound3 ([3‐(3‐carbamoylpyrrol‐1‐yl)phenyl] N ‐(5‐phenylpentyl)carbamate) to lack any cytotoxic effect, while all three showed the ability to decrease oxidative stress by reducing the expression of the redox‐sensitive transcription factor NF‐κB. Encouraged by these data, these compounds were studied in vivo and were dosed orally in a mouse model of neuropathic pain. At 10 mg kg −1 all the compounds were able to relieve the hypersensitivity induced by oxaliplatin. Abstract : By rational design, aiming at the discovery of selective FAAH inhibitors to obtain therapeutic effects against neuropathic pain, we developed a series of compounds characterized by functionalized tricyclic scaffolds. The most potent nontoxic FAAH inhibitors5 h and5 i were found to decrease oxidative stress by lowering the expression of NF‐κB and to show efficacy in a mouse model of neuropathic pain, relieving the hypersensitivity induced by oxaliplatin.